2020
DOI: 10.1088/1361-6641/abc28e
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, design, and simulation of Schottky diodes based on ultrananocrystalline diamond composite films

Abstract: In this study, heterojunction diodes based on ultrananocrystalline diamond/hydrogenated amorphous carbon (UNCD/a-C:H) composite films, grown on Si substrates using the coaxial arc plasma deposition method, were modeled, characterized, and investigated. Calibrated material parameters, extracted from experimental analysis of nitrogen-doped (n-type) UNCD/a-C:H/p-type Si heterojunctions, were fed to the device model. Design of vertical geometry Pd/n-type UNCD/a-C:H Schottky diodes was proposed using a two-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…A coaxial arc plasma gun (CAPG) equipped with pure graphite targets was fixed inside the deposition chamber. A capacitor of 720 μF and 100 V power supply was used to operate the CAPG [21][22][23][24][25][26][27][28][29][30][31][32] . The chamber was initially evacuated to a pressure less than 10 -5 Pa, using a turbo molecular pump.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A coaxial arc plasma gun (CAPG) equipped with pure graphite targets was fixed inside the deposition chamber. A capacitor of 720 μF and 100 V power supply was used to operate the CAPG [21][22][23][24][25][26][27][28][29][30][31][32] . The chamber was initially evacuated to a pressure less than 10 -5 Pa, using a turbo molecular pump.…”
Section: Methodsmentioning
confidence: 99%
“…The surface states density in Pd/n-type UNCD/a-C:H films was evaluated to be 1.7 × 10 15 cm -2 eV -1 for the slow response states, which decreased to 2.0 × 10 14 cm -2 eV -1 for the high-frequency response states [22] . Although the electrical and optical properties of N 2 -doped UN-CD/a-C:H films grown by the CAPD method have been extensively studied [23][24][25][26][27][28][29][30][31][32] , there have been very limited reports on defects in these films. In this study, defect properties and energy-distributed trap density-of-states (DOS) in UNCD/a-C:H films have been experimentally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that they (π C=N bonds) contribute to the enhancement of electrical conductivity due to the generation of unpaired electrons. We extensively investigated the electrical characteristics of n-type (UNCD/a-C:H)/p-Si heterojunctions fabricated by the CAPG method utilizing current-voltage (I-V) measurements under different conditions of temperatures and illuminations [16]- [21]. On the other hand, the contributions of the nanodiamond grains and the GBs to the electrical properties of nitrogen-doped (UNCD/a-C:H) have not been comprehensively investigated yet.…”
Section: Introductionmentioning
confidence: 99%